Carbonate‐Induced Electrosynthesis of Hydrogen Peroxide via Two‐Electron Water Oxidation. Issue 4 (2nd February 2022) - Mavrikis, Sotirios; Göltz, Maximilian; Rosiwal, Stefan; Wang, Ling; Ponce de León, Carlos
Abstract: Electrochemical synthesis of hydrogen peroxide (H2 O2 ), via the two‐electron water oxidation reaction (2e − WOR), is an attractive method for the sustainable production of valuable chemicals in place of oxygen during water electrolysis. While the majority of 2e − WOR studies have focussed on electrocatalyst design, little research has been carried out on the selection of the supporting electrolyte. In this work, we investigate the impact of potassium carbonate (K2 CO3 ) electrolytes, and their key properties, on H2 O2 production. We found that at electrolyte pH values (>9.5) where the carbonate anion (CO3 2− ) was prevalent in the mixture, a 26.5 % increase in the Faraday efficiency (%FE) for H2 O2 production was achieved, compared to bicarbonate (HCO3 − ) dominant solutions. Utilising boron‐doped diamond (BDD) in highly concentrated K2 CO3 solutions, current densities of up to 511 mA cm −2 (in 4 m ) and %FEs of 91.5 % (in 5 m) could be attained. The results presented in this work highlight the influence of CO3 2− on electrochemical H2 O2 generation via the 2e − WOR and provide novel pathways to produce desirable commodities at the anode during electrochemical water splitting. Abstract : Optimising anodic H2 O2 electrosynthesis : Carbonate‐based electrolytes are found to considerably enhance hydrogen peroxide production via the two‐electron water oxidation reaction, with notable Faraday efficiencies attained when using boron doped diamond anodes in highly concentrated potassium carbonate aqueous solutions.